The Effectiveness of Range of Motion Exercise in Reducing Serum Uric Acid Levels in Individuals with Hyperuricemia : a Non-Pharmacological Strategy for Preventing Cardiovascular and Renal Complications: Exploring the Role of Physical Activity in Managing Metabolic Risk - Yusnaini, Rika -; Iskandar, Iskandar; Junaidi, Junaidi; Masyudi, Masyudi (Program Studi Kedokteran Fakultas Kedokteran Universitas Malikussaleh, 2025)
Hyperuricemia has been associated with various health conditions, including hypertension and kidney disease. However, the causal relationship between uric acid and the development of these complications remains a topic of debate. Some studies suggest that elevated uric acid levels may play a direct role in the pathogenesis of hypertension through inflammatory mechanisms, endothelial dysfunction, and oxidative stress. In contrast, other studies argue that uric acid is merely a risk biomarker without a direct pathophysiological effect. In this context, physical activity has been extensively studied as a non-pharmacological intervention for arthritis and as a means to improve cardiovascular health. This study aims to explore the effectiveness of physical activity, particularly Range of Motion (ROM) exercises, in reducing serum uric acid levels in individuals with hyperuricemia. The methodology involved an eight-week ROM intervention with an evaluation of serum uric acid levels before and after the intervention. The results indicated that regular physical activity significantly contributed to the reduction of serum uric acid levels (p < 0.001), which may be associated with increased uric acid excretion through the kidneys. These findings support the role of physical activity as a potential strategy for managing hyperuricemia while also providing further insights into the relationship between uric acid, hypertension, and kidney health.